Fibroblast Growth Factor Receptor 3 (FGFR3)–Analyses of the S249C Mutation and Protein Expression in Primary Cervical Carcinomas - Haiyan Dai; Ruth Holm; Gunnar B. Kristensen; Vera M. Abeler; Anne‐Lise Børresen‐Dale; Åslaug Helland (Analytical Cellular Pathology)
Fibroblast growth factor receptor 3 (FGFR3) seems to play an inhibitory role in bone development, as activating mutations in the gene underlie disorders such as achondroplasia and thanatophoric dysplasia. Findings from multiple myeloma (MM) indicate that FGFR3 also can act as an oncogene, and mutation of codon 249 in the fibroblast growth factor receptor 3 (FGFR3) gene was recently detected in 3/12 primary cervical carcinomas. We have analysed 91 cervical carcinomas for this specific S249C mutation using amplification created restriction site methodology (ACRS), and detected no mutations. Immunohistochemistry was performed on 73 of the tumours. Reduced protein staining was seen in 43 (58.8%) samples. Six of the tumours (8.2%) revealed increased protein staining compared with normal cervical tissue. These patients had a better prognosis than those with reduced or normal levels, although not statistically significant. This report weakens the hypothesis of FGFR3 as an oncogene of importance in cervical carcinomas.